Facebook as “third space”: Triggers of political talk in news about nonpublic affairs - Siles González, Ignacio (2020)
This paper builds on recent work on “third spaces” to analyze political talk in comments on news about nonpublic affairs. It draws on content and discourse analyses of comments on news published by a leading Costa Rican media organization on Facebook. The article develops five categories of issues that triggered political talk (institutionality, identity, political inclinations, factual aspects, and criticism of the media) and examines the discursive strategies through which these comments became political. This allowed to broaden understanding of the political relevance of discussions about nonpublic affairs on social media.